Regression analysis of the symptoms - Gruden-Pokupec, Josipa-Sanja (Array, 2009)
Abstract: Stomatopyrosis of 'burning mouth' syndrome, in a narrower sense of definition, is a condition characterized by sensation of burning and heating in mouth, despite its normal mucosa. This research has been directed towards treatment of stomatopyrosis, putting emphasis on the implementation of psychopharmacotherapy and psychotherapy. The research was conducted on altogether 120 respondents suffering from stomatopyrosis. The respondents were divided into two equal groups: each one comprising 60 members. All the respondents were treated by means of a standard topical therapy. All the patients were assessed clinically and by means of psychological tests measuring depression and anxiety four times: once before the treatment, after one month, after two months and after four months since the beginning of the treatment. The acquired data were afterwards statistically processed. Our research led to the conclusion that stomatopyrosis occurs with elderly people, primarily women.